2013
DOI: 10.1007/s12529-013-9293-2
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Variability in Stress, Sleep Duration, and Sleep Quality Across the Distribution of Body Mass Index: Insights from Quantile Regression

Abstract: Purpose This study investigates whether sleep and stress are associated with body mass index (BMI) respectively, explores whether the combination of stress and sleep is also related to BMI, and demonstrates a thorough picture of how these associations above vary across the distribution of BMI values. Methods We analyze the data from 3,318 men and 6,689 women in the Philadelphia area using quantile regression (QR) to evaluate the relationships between sleep, stress, and obesity by gender. Results Our substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Our data showing large sex differences in caloric intake are consistent with population evidence suggesting that men are more susceptible to weight gain resulting from sleep loss (19)(20)(21) and with our experimental findings that men gained more weight than women did during an SR protocol (9). As a result of their larger mass, men eat more than women do (37); indeed, we showed that men consumed more calories during baseline and SR than did women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data showing large sex differences in caloric intake are consistent with population evidence suggesting that men are more susceptible to weight gain resulting from sleep loss (19)(20)(21) and with our experimental findings that men gained more weight than women did during an SR protocol (9). As a result of their larger mass, men eat more than women do (37); indeed, we showed that men consumed more calories during baseline and SR than did women.…”
Section: Discussionsupporting
confidence: 91%
“…This pattern has also been observed in adolescents (22,23) and children (24,25). Using self-report surveys, 2 recent population studies showed that sleep duration was inversely associated with BMI in men only, whereas poor sleep quality was positively associated with BMI in women only (20,21). In a prospective cohort study, short sleep duration was associated with weight gain and the development of obesity at 1 y follow-up in men but not women (26).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Spaeth et al [48] found that men exhibited a greater increase in daily caloric intake during sleep restriction as a result of consuming more calories during late-night hours than women did. Population studies showed that sleep duration was inversely associated with BMI in men only, whereas poor sleep quality was positively associated with BMI in women only [49,50]. Due to the cross-sectional nature of the study, a causal connection between sleep duration and the risk of obesity cannot be fully explained.…”
Section: Discussionmentioning
confidence: 86%
“…Among the few studies that collected information on different sleep characteristics, only a minority of them attempted to control for other sleep aspects. For example, three studies adjusted for sleep duration [5, 9, 11] and one study adjusted for snoring [6] in their analysis on sleep quality and adiposity, and reported that the association between poor sleep quality and higher BMI remained after the additional adjustment. In our study, after simultaneously including all three sleep variables in the model, we found that snoring remained strongly associated with adiposity regardless of sleep duration and quality, suggesting that this relationship is robust and may involve distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%